Polycrystalline carbonate cement and preparation method thereof

Through the preparation method of polycrystalline carbonate cement, regenerated micro powder, salt lake magnesium slag and α-aminopropionic acid are used to generate stable carbonate products, which solves the problems of high resource consumption and high pollution in silicate cement production, and realizes the problem of high resource consumption and high pollution in silicate cement production. The preparation of low-carbon emissions and high-performance concrete is carried out.

CN118459182BActive Publication Date: 2025-02-25CHINA BUILDING MATERIALS ACADEMY CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410560947.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-08
Publication Date
2025-02-25
Estimated Expiration
2044-05-08

AI Technical Summary

Technical Problem

The existing silicate cement production has problems of high resource consumption, high energy consumption and high pollution, and is highly dependent on natural resources, affecting the carbon emission reduction target.

Method used

The preparation method of polycrystalline carbonate cement is adopted to generate stable carbonate products by regenerating micro powder, salt lake magnesium slag and α-aminopropionic acid, including different crystal forms, and the content of salt lake magnesium slag is changed to improve the cement Toughness and durability.

Benefits of technology

High-performance concrete with low carbon emissions and low production energy consumption has been achieved, reducing dependence on natural resources, reducing energy consumption and pollution emissions, and promoting the development of the circular economy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005169376310000091
    Figure GDA0005169376310000091
Patent Text Reader

Abstract

The present application relates to the field of carbonate cement, and specifically discloses a polycrystalline carbonate cement and a preparation method thereof, wherein the cement is prepared by carbonizing raw materials, and the raw materials include the following components by weight: 700-900 parts of recycled micropowder, 100-300 parts of salt lake magnesium slag, 13.35-66.75 parts of α-aminopropionic acid, 117-350 parts of water, and 1400-1500 parts of filler. The present application can not only achieve low carbon emissions and lower production energy consumption, but also obtain concrete with good mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of carbonate cement, and more specifically, to a polycrystalline carbonate cement and a preparation method thereof. Background Art

[0002] my country has a high output and large amount of silicate cement, accounting for more than 60% of the global cement production. However, the production of silicate cement has problems of high resource consumption, high energy consumption and high pollution. In the production of silicate cement, the high temperature conditions required for the clinker calcination process have a huge demand for energy. According to the International Energy Agency (IEA), the cement industry accounts for about 7% of the global industrial terminal energy consumption. Secondly, the calcination process involved in the production of silicate cement not only requires a lot of energy, but also leads to a large amount of carbon dioxide emissions. According to IEA data, the cement industry accounts for about 8% of global carbon dioxide emissions. Finally, silicate cement production is highly dependent on natural resources such as limestone and clay. Statistics show that in order to produce one ton of Portland cement, 2 to 3 tons of limestone and clay are usually consumed. In the context of achieving "carbon peak" and "carbon neutrality" proposed in 2020, the cement industry faces severe challenges. Therefore, the "2050 Cement Technology Roadmap" jointly developed by the International Energy Agency and the Cement Sustainable Development Initiative focuses on the main carbon emission reduction pathways in the cement industry, pointing out that the development of low-carbon cementitious materials is an important technical path for the cement industry to reduce CO2 emissions. Therefore, the development and growth of new low-carbon cement-based materials and their preparation technologies is the key to achieving carbon emission reduction in the cement industry and implementing the "dual carbon" strategy.

[0003] Due to the rapid economic development, the process of urban construction and urbanization has been accelerated. The large-scale demolition and reconstruction of old buildings and the renovation of cement concrete pavements have resulted in an increasing amount of waste concrete. Recycled concrete, which is made by partially or completely replacing natural aggregates with recycled aggregates obtained by crushing, cleaning, screening and grading of waste concrete test blocks, has been greatly developed. While strengthening the recycling of recycled aggregates, micropowders accounting for about 10%-20% of the recycled aggregates will be generated during the crushing and screening of recycled aggregates. Some fine particles float in the air and cause serious dust pollution. Therefore, the treatment and utilization of recycled micropowders have received extensive attention.

[0004] In addition, my country has rich salt lake resources, which are the largest treasure trove of inorganic salt resources such as potassium, magnesium and lithium in my country. At present, the development of salt lake resources in my country is mainly focused on the production of potash fertilizers and lithium carbonate. In the production of potash fertilizers and lithium carbonate, a large amount of salt lake magnesium slag will be produced as a by-product. These salt lake magnesium slags are basically piled up in the salt lake as waste, resulting in local enrichment of magnesium salts, which seriously affects the ecological environment of the Qinghai Salt Lake, the so-called "magnesium harm". This not only causes a waste of resources, but also destroys the resource structure of the salt lake to a certain extent, affecting the sustainable development and utilization of salt lake resources. Therefore, solving the problem of the utilization of salt lake magnesium slag has become a major scientific and technological issue for achieving the sustainable development of salt lake resources.

[0005] Therefore, it is a very important topic to make full use of resources such as recycled micropowder and salt lake magnesium slag to prepare a high-performance concrete under the premise of reducing low-carbon emissions. Summary of the invention

[0006] The present application provides a polycrystalline carbonate cement and a preparation method thereof, which can not only achieve low carbon emissions and lower production energy consumption, but also the obtained concrete has good mechanical properties.

[0007] In a first aspect, the present application provides a polycrystalline carbonate cement, which adopts the following technical solution:

[0008] A polycrystalline carbonate cement is prepared by carbonizing raw materials, wherein the raw materials comprise the following components by weight: 700-900 parts of recycled micropowder, 100-300 parts of salt lake magnesium slag, 13.35-66.75 parts of alpha-aminopropionic acid, 117-350 parts of water, and 1400-1500 parts of fillers.

[0009] By adopting the above technical scheme, the present application utilizes the mineral carbonation technology, and generates stable carbonate products through the carbonization of regenerated micropowder, salt lake magnesium slag and α-aminopropionic acid, and these carbonate products contain different crystal forms; at the same time, the present application achieves the goal of preparing carbonate cement with good toughness and excellent durability by changing the content of salt lake magnesium slag. The main reaction mechanism involved in the present application is: the regenerated micropowder contains a small amount of calcium hydroxide, the salt lake magnesium slag contains a large amount of magnesium oxide and magnesium hydroxide, the two are mixed and ground to form a powder, a small amount of α-aminopropionic acid is added to form a solution mixed with water, the solution and the powder are mixed to form a slurry, and the slurry is placed in CO2 for carbonization to slowly generate carbonates. These carbonates include calcite, magnesium calcite and aragonite. In this process, it is mainly the amino group and carboxyl group in α-aminopropionic acid that are adsorbed on different crystal faces of calcium carbonate, and the unstable vaterite crystals are induced when the carboxyl group and the amino group work synergistically. At the same time, the salt lake magnesium slag contains a large amount of magnesium oxide that releases Mg2+. Under the effect of Mg2+, unstable vaterite crystals can realize the conversion of different crystal forms, and along with the concentration variation of Mg2+, unstable vaterite crystals can continue to become calcite for the most part, and a small part is transformed into needle-like aragonite structure, which helps the raising of the toughness of carbonate cement.Continue to raise the concentration of salt lake magnesium slag, part of calcite can also be transformed into magnesium calcite, and this is mainly due to the Ca2+ of calcite crystals being replaced by Mg2+ in the kink position, thereby causing the formation of magnesium calcite.The formation of magnesium calcite can improve the microstructure of carbonate cement, thereby improves the mechanical property and the durability of cement material.Therefore, the polycrystalline carbonate cement prepared by the present application, compared to traditional cement, has some obvious advantages of polycrystalline carbonate cement.

[0010] Furthermore, the carbonization operation utilizes CO2 to carbonize the raw materials, and the flow rate of CO2 is 1-2m3 / h.

[0011] Furthermore, the particle size of the regenerated micro powder is 20-75 microns. The particle size of the salt lake magnesium slag is 20-75 microns. The filler is river sand, the fineness of the river sand is medium sand, and the fineness modulus is 2.5-2.8.

[0012] In a second aspect, the present application provides a method for preparing polycrystalline carbonate cement, which adopts the following technical solution:

[0013] A method for preparing polycrystalline carbonate cement comprises the following steps:

[0014] An α-aminopropionic acid aqueous solution is added to the regenerated micro powder and salt lake magnesium slag, stirred to obtain a slurry, and then a filler is added, mixed evenly and then naturally cured. After natural curing, the mixture is moved into a carbonization curing box for carbonization curing to obtain polycrystalline carbonate cement.

[0015] Furthermore, during carbonization curing, the carbonization time is 24-48 hours.

[0016] Furthermore, during carbonization curing, the ambient humidity is 50-60% and the temperature is 20-25°C.

[0017] Furthermore, the conditions for natural curing are: an ambient humidity of 50-60%, a temperature of 20-25°C, and a time of 24-48 hours.

[0018] In summary, this application has the following beneficial effects:

[0019] 1. This application utilizes CO2, recycled micropowder, salt lake magnesium slag and α-aminopropionic acid, and controls the dosage of relevant components to react and generate stable carbonate products with a suitable amount and type of polycrystalline carbonates, so that the cement has good toughness, mechanical properties and durability.

[0020] 2. The production process of carbonate cement in this application generates less carbon dioxide emissions. Compared with the high-temperature calcination process of traditional cement, the production of carbonate cement can be more environmentally friendly and help mitigate climate change.

[0021] 3. The raw materials used in the carbonate cement of this application are industrial waste, which can reduce the dependence on natural resources. This helps to reduce the impact of mining on the environment and promote the development of the circular economy.

[0022] 4. Compared with traditional cement, the production process of carbonate cement usually requires lower temperature and energy, thus reducing energy consumption. This helps to improve the energy efficiency of production.

[0023] 5. Carbonate cement products have higher strength and earlier strength development, which can improve construction efficiency and reduce the amount of concrete used, helping to reduce the overall building carbon footprint. DETAILED DESCRIPTION

[0024] The present application is further described in detail below with reference to the embodiments.

[0025] In the embodiment of the present application, a polycrystalline carbonate cement is provided, and the raw materials include the following components by weight: 700-900 parts of recycled micropowder, 100-300 parts of salt lake magnesium slag, 13.35-66.75 parts of α-aminopropionic acid, 117-350 parts of water, and 1400-1500 parts of filler. The particle size of the recycled micropowder and the salt lake magnesium slag is 20-75 microns. The filler is river sand, the fineness of the river sand is medium sand, the fineness modulus is 2.5-2.8, and the fineness modulus in this embodiment is 2.65.

[0026] The present application also provides a method for preparing polycrystalline carbonate cement, comprising the following steps:

[0027] An α-aminopropionic acid aqueous solution is added to the regenerated micro powder and salt lake magnesium slag, stirred to obtain a slurry, and then a filler is added, mixed evenly and then naturally cured. After natural curing, the mixture is moved into a carbonization curing box for carbonization curing to obtain polycrystalline carbonate cement.

[0028] Furthermore, during carbonization curing, the flow rate of CO2 is 1-2m 3 / h, carbonization time is 24-48 hours, ambient humidity is 50-60%, temperature is 20-25°C. In natural curing, the ambient humidity is 50-60%, the temperature is 20-25°C, and the time is 24-48 hours.

[0029] The following is an explanation through specific examples.

[0030] Example 1

[0031] This embodiment provides a polycrystalline carbonate cement, the raw materials of which include the following components: 800g of regenerated micropowder, 200g of salt lake magnesium slag, 13.35g of α-alanine, 117g of water, and 1500g of filler, wherein the particle sizes of the regenerated micropowder and the salt lake magnesium slag are both 20-50 microns.

[0032] This embodiment also provides a method for preparing polycrystalline carbonate cement, comprising the following steps:

[0033] A method for preparing polycrystalline carbonate cement comprises the following steps:

[0034] An α-aminopropionic acid aqueous solution is added to the regenerated micro powder and salt lake magnesium slag, stirred to obtain a slurry, and then a filler is added, mixed evenly and poured into a mold for natural curing. After natural curing, the mixture is moved into a carbonization curing box for carbonization curing to obtain polycrystalline carbonate cement.

[0035] Specifically, during carbonization curing, the flow rate of CO2 is 1.5m 3 / h, carbonization time is 36 hours, ambient humidity is 50-60%, temperature is 20-25°C. In natural curing, ambient humidity is 50-60%, temperature is 20-25°C, and time is 24 hours.

[0036] Example 2

[0037] This embodiment provides a polycrystalline carbonate cement, the raw materials of which include the following components: 800g of regenerated micropowder, 200g of salt lake magnesium slag, 26.7g of α-alanine, 117g of water, and 1500g of filler, wherein the particle sizes of the regenerated micropowder and the salt lake magnesium slag are both 20-50 microns.

[0038] This embodiment also provides a method for preparing polycrystalline carbonate cement, comprising the following steps:

[0039] A method for preparing polycrystalline carbonate cement comprises the following steps:

[0040] An α-aminopropionic acid aqueous solution is added to the regenerated micro powder and salt lake magnesium slag, stirred to obtain a slurry, and then a filler is added, mixed evenly and poured into a mold for natural curing. After natural curing, the mixture is moved into a carbonization curing box for carbonization curing to obtain polycrystalline carbonate cement.

[0041] Specifically, during carbonization curing, the flow rate of CO2 is 1.5m 3 / h, carbonization time is 36 hours, ambient humidity is 50-60%, temperature is 20-25°C. In natural curing, ambient humidity is 50-60%, temperature is 20-25°C, and time is 24 hours.

[0042] Example 3

[0043] This embodiment provides a polycrystalline carbonate cement, the raw materials of which include the following components: 800g of regenerated micropowder, 200g of salt lake magnesium slag, 40.05g of α-alanine, 117g of water, and 1500g of filler, wherein the particle sizes of the regenerated micropowder and the salt lake magnesium slag are both 20-50 microns.

[0044] This embodiment also provides a method for preparing polycrystalline carbonate cement, comprising the following steps:

[0045] A method for preparing polycrystalline carbonate cement comprises the following steps:

[0046] An α-aminopropionic acid aqueous solution is added to the regenerated micro powder and salt lake magnesium slag, stirred to obtain a slurry, and then a filler is added, mixed evenly and poured into a mold for natural curing. After natural curing, the mixture is moved into a carbonization curing box for carbonization curing to obtain polycrystalline carbonate cement.

[0047] Specifically, during carbonization curing, the flow rate of CO2 is 1.5m 3 / h, carbonization time is 36 hours, ambient humidity is 50-60%, temperature is 20-25°C. In natural curing, ambient humidity is 50-60%, temperature is 20-25°C, and time is 24 hours.

[0048] Example 4

[0049] This embodiment provides a polycrystalline carbonate cement, the raw materials of which include the following components: 800g of regenerated micropowder, 200g of salt lake magnesium slag, 53.4g of α-alanine, 117g of water, and 1500g of filler, wherein the particle sizes of the regenerated micropowder and the salt lake magnesium slag are both 20-50 microns.

[0050] This embodiment also provides a method for preparing polycrystalline carbonate cement, comprising the following steps:

[0051] A method for preparing polycrystalline carbonate cement comprises the following steps:

[0052] An α-aminopropionic acid aqueous solution is added to the regenerated micro powder and salt lake magnesium slag, stirred to obtain a slurry, and then a filler is added, mixed evenly and poured into a mold for natural curing. After natural curing, the mixture is moved into a carbonization curing box for carbonization curing to obtain polycrystalline carbonate cement.

[0053] Specifically, during carbonization curing, the flow rate of CO2 is 1.5m 3 / h, carbonization time is 36 hours, ambient humidity is 50-60%, temperature is 20-25°C. In natural curing, ambient humidity is 50-60%, temperature is 20-25°C, and time is 24 hours.

[0054] Example 5

[0055] This embodiment provides a polycrystalline carbonate cement, the raw materials of which include the following components: 800g of regenerated micropowder, 200g of salt lake magnesium slag, 66.75g of α-alanine, 117g of water, and 1500g of filler, wherein the particle sizes of the regenerated micropowder and the salt lake magnesium slag are both 20-50 microns.

[0056] This embodiment also provides a method for preparing polycrystalline carbonate cement, comprising the following steps:

[0057] A method for preparing polycrystalline carbonate cement comprises the following steps:

[0058] An α-aminopropionic acid aqueous solution is added to the regenerated micro powder and salt lake magnesium slag, stirred to obtain a slurry, and then a filler is added, mixed evenly and poured into a mold for natural curing. After natural curing, the mixture is moved into a carbonization curing box for carbonization curing to obtain polycrystalline carbonate cement.

[0059] Specifically, during carbonization curing, the flow rate of CO2 is 1.5m 3 / h, carbonization time is 36 hours, ambient humidity is 50-60%, temperature is 20-25°C. In natural curing, ambient humidity is 50-60%, temperature is 20-25°C, and time is 24 hours.

[0060] Example 6

[0061] This embodiment provides a polycrystalline carbonate cement, the raw materials of which include the following components: 700g of regenerated micropowder, 300g of salt lake magnesium slag, 66.75g of α-alanine, 117g of water, and 1500g of filler, wherein the particle sizes of the regenerated micropowder and the salt lake magnesium slag are both 20-50 microns.

[0062] This embodiment also provides a method for preparing polycrystalline carbonate cement, comprising the following steps:

[0063] A method for preparing polycrystalline carbonate cement comprises the following steps:

[0064] An α-aminopropionic acid aqueous solution is added to the regenerated micro powder and salt lake magnesium slag, stirred to obtain a slurry, and then a filler is added, mixed evenly and poured into a mold for natural curing. After natural curing, the mixture is moved into a carbonization curing box for carbonization curing to obtain polycrystalline carbonate cement.

[0065] Specifically, during carbonization curing, the flow rate of CO2 is 1.5m 3 / h, carbonization time is 36 hours, ambient humidity is 50-60%, temperature is 20-25°C. In natural curing, ambient humidity is 50-60%, temperature is 20-25°C, and time is 24 hours.

[0066] Example 7

[0067] This embodiment provides a polycrystalline carbonate cement, the raw materials of which include the following components: 800g of regenerated micropowder, 100g of salt lake magnesium slag, 66.75g of α-alanine, 117g of water, and 1500g of filler, wherein the particle sizes of the regenerated micropowder and the salt lake magnesium slag are both 20-50 microns.

[0068] This embodiment also provides a method for preparing polycrystalline carbonate cement, comprising the following steps:

[0069] A method for preparing polycrystalline carbonate cement comprises the following steps:

[0070] An α-aminopropionic acid aqueous solution is added to the regenerated micro powder and salt lake magnesium slag, stirred to obtain a slurry, and then a filler is added, mixed evenly and poured into a mold for natural curing. After natural curing, the mixture is moved into a carbonization curing box for carbonization curing to obtain polycrystalline carbonate cement.

[0071] Specifically, during carbonization curing, the flow rate of CO2 is 1.5m 3 / h, carbonization time is 36 hours, ambient humidity is 50-60%, temperature is 20-25°C. In natural curing, ambient humidity is 50-60%, temperature is 20-25°C, and time is 24 hours.

[0072] Example 8

[0073] This embodiment provides a polycrystalline carbonate cement, the raw materials of which include the following components: 700g of regenerated micropowder, 200g of salt lake magnesium slag, 44.3g of α-alanine, 350g of water, and 1400g of filler, wherein the particle sizes of the regenerated micropowder and the salt lake magnesium slag are both 45-75 microns.

[0074] This embodiment also provides a method for preparing polycrystalline carbonate cement, comprising the following steps:

[0075] A method for preparing polycrystalline carbonate cement comprises the following steps:

[0076] An α-aminopropionic acid aqueous solution is added to the regenerated micro powder and salt lake magnesium slag, stirred to obtain a slurry, and then a filler is added, mixed evenly and poured into a mold for natural curing. After natural curing, the mixture is moved into a carbonization curing box for carbonization curing to obtain polycrystalline carbonate cement.

[0077] Specifically, during carbonization curing, the flow rate of CO2 is 1m 3 / h, carbonization time is 48 hours, ambient humidity is 50-60%, temperature is 20-25℃. During natural curing, ambient humidity is 50-60%, temperature is 20-25℃, and time is 48 hours.

[0078] Example 9

[0079] This embodiment provides a polycrystalline carbonate cement, the raw materials of which include the following components: 900g of regenerated micropowder, 250g of salt lake magnesium slag, 33.5g of α-alanine, 200g of water, and 1600g of filler, wherein the particle sizes of the regenerated micropowder and the salt lake magnesium slag are both 20-50 microns.

[0080] This embodiment also provides a method for preparing polycrystalline carbonate cement, comprising the following steps:

[0081] A method for preparing polycrystalline carbonate cement comprises the following steps:

[0082] An α-aminopropionic acid aqueous solution is added to the regenerated micro powder and salt lake magnesium slag, stirred to obtain a slurry, and then a filler is added, mixed evenly and poured into a mold for natural curing. After natural curing, the mixture is moved into a carbonization curing box for carbonization curing to obtain polycrystalline carbonate cement.

[0083] Specifically, during carbonization curing, the flow rate of CO2 is 2m 3 / h, carbonization time is 24 hours, ambient humidity is 50-60%, temperature is 20-25℃. During natural curing, ambient humidity is 50-60%, temperature is 20-25℃, and time is 24 hours.

[0084] The difference between Example 10 and Example 5 is that, specifically, during carbonization curing, the flow rate of CO2 is 2.5 m 3 / h, carbonization time is 36 hours, ambient humidity is 50-60%, and temperature is 20-25℃.

[0085] The difference between Example 11 and Example 5 is that, specifically, during carbonization curing, the flow rate of CO2 is 1.5 m 3 / h, carbonization time is 72 hours, ambient humidity is 50-60%, and temperature is 20-25℃.

[0086] Comparative Example

[0087] The difference between Comparative Example 1 and Example 5 is that the raw materials of polycrystalline carbonate cement include the following components: 1000 g of recycled micropowder, 0 g of salt lake magnesium slag, 66.75 g of α-aminopropionic acid, and 117 g of water.

[0088] The difference between Comparative Example 2 and Example 5 is that the raw materials of polycrystalline carbonate cement include the following components: 800 g of recycled micropowder, 200 g of salt lake magnesium slag, 0 g of α-aminopropionic acid, and 117 g of water.

[0089] The difference between Comparative Example 3 and Example 5 is that the raw materials of polycrystalline carbonate cement include the following components: 800 g of regenerated micropowder, 200 g of salt lake magnesium slag, 70 g of α-aminopropionic acid, and 117 g of water.

[0090] The difference between Comparative Example 4 and Example 5 is that the raw materials of polycrystalline carbonate cement include the following components: 800 g of regenerated micropowder, 200 g of salt lake magnesium slag, 10 g of α-aminopropionic acid, and 117 g of water.

[0091] The difference between Comparative Example 5 and Example 5 is that the raw materials of polycrystalline carbonate cement include the following components: 600 g of regenerated micropowder, 400 g of salt lake magnesium slag, 66.75 g of α-aminopropionic acid, and 117 g of water.

[0092] Performance Testing

[0093] The performance of the cement products obtained in the examples and comparative examples was tested as follows:

[0094] Compression / flexural strength test: The mechanical test was carried out using the method of concrete mechanical properties test method standard GB / T 50081-2002, and the sample size was 40*40*160mm.

[0095] Free expansion rate measurement: A 40*40*160 mortar test block with copper heads embedded at both ends and no external constraints is used. The mold is a detachable cast iron mold. The shrinkage heads are placed in the reserved holes on both sides and the slurry is poured. The measurement is carried out using a ratio meter. The experimental method is based on the "Basic Performance Test Method of Building Mortar" (JGJ70-2009) specification.

[0096] Table 1 Performance test table of embodiments and comparative examples

[0097]

[0098] Analysis of the performance of the embodiment shows that the cement products obtained in the present application not only have higher strength and earlier strength development, can improve construction efficiency, and reduce the amount of concrete used, but also have the advantages of low carbon emissions, renewable raw materials, and lower production energy consumption. This is because in the cement of the present application, recycled micropowder, salt lake magnesium slag, α-aminopropionic acid, etc. are used as raw materials, and carbonized with carbon dioxide of a suitable flow rate to obtain the final cement products. In the carbonization process, under the synergistic effect of salt lake magnesium slag, α-aminopropionic acid, etc., the cement of the present application generates carbonates including calcite, magnesium calcite and aragonite, and a suitable number of carbonates of different crystal forms cooperate with each other, effectively improving the performance of the cement.

[0099] The performance of Example 1-5 is analyzed and found that, with the gradual increase of the amount of α-alanine, the performance of cement does not show a trend of gradual improvement, wherein, the performance of Example 4 is the best. Meanwhile, the performance of Example 5-7 is analyzed and found that with the gradual increase of the amount of salt lake magnesium slag, the performance of cement does not show a trend of gradual improvement, wherein, the performance of Example 5 is the best. In addition, the performance of Comparative Example 1 and Comparative Example 2 is observed and found that, without adding salt lake magnesium slag, or without adding α-alanine, the final cement performance all decreases. This illustrates that the amino and carboxyl groups in α-alanine are adsorbed on different crystal faces of calcium carbonate, and unstable vaterite crystals are induced when the carboxyl group and the amino group act synergistically, and the Mg2+ released by the salt lake magnesium slag induces the formation of aragonite structure and magnesium calcite, which is conducive to improving the mechanical properties of cement materials, etc. However, for the use of salt lake magnesium slag and α-alanine, it is not the more the better, because the present application not only promotes the formation of polymorphic carbonate, but also has a matching relationship between different crystal forms, and the matching between the appropriate amount of crystal forms is more conducive to the improvement of cement performance.

[0100] Furthermore, by analyzing the performance of Examples 3-4, it can be found that excessive or insufficient use of α-aminopropionic acid, and excessive use of salt lake magnesium slag, all cause the performance of cement materials to decline to varying degrees, further proving that the amount of α-aminopropionic acid and salt lake magnesium slag affects the amount and stability of different crystalline carbonates formed, and the technical solution of the present application can form more stable and appropriate amounts of different crystalline carbonates, which is helpful to improve the performance of cement.

[0101] Regarding the process of carbonization of raw materials to form different crystalline carbonates, the present application further explores the effect of the degree of carbonization on the performance of cement. By observing the performance of Example 10 and Example 11 and comparing them with Example 5, it is found that excessively high or low degrees of carbonization will also affect the performance of cement materials. This is because the degree of carbonization will also affect the formation of different crystalline carbonates.

[0102] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A polycrystalline carbonate cement, characterized in that: The cement is prepared by carbonizing raw materials, and the raw materials include the following components by weight: 700-900 parts of regenerated micropowder, 100-300 parts of salt lake magnesium slag, 13.35-66.75 parts of alpha-aminopropionic acid, 117-350 parts of water, and 1400-1500 parts of fillers.

2. A polycrystalline carbonate cement according to claim 1, characterized in that: The carbonization operation is to use CO2 to carbonize the raw materials, and the flow rate of CO2 is 1-2m 3 / h.

3. The polycrystalline carbonate cement according to claim 1, characterized in that: The particle size of the regenerated micro powder is 20-75 microns.

4. The polycrystalline carbonate cement according to claim 1, characterized in that: The particle size of the salt lake magnesium slag is 20-75 microns.

5. The polycrystalline carbonate cement according to claim 1, characterized in that: The filler is river sand, the fineness of the river sand is medium sand, and the fineness modulus is 2.5-2.

8.

6. A method for preparing a polycrystalline carbonate cement according to any one of claims 1 to 5, characterized in that: The following steps are involved: An α-aminopropionic acid aqueous solution is added to the regenerated micro powder and salt lake magnesium slag, stirred to obtain a slurry, and then a filler is added, mixed evenly and then naturally cured. After natural curing, the mixture is moved into a carbonization curing box for carbonization curing to obtain polycrystalline carbonate cement.

7. The method for preparing polycrystalline carbonate cement according to claim 6, characterized in that: During carbonization curing, the carbonization time is 24-48 hours.

8. The method for preparing polycrystalline carbonate cement according to claim 6, characterized in that: During carbonization curing, the ambient humidity is 50-60% and the temperature is 20-25°C.

9. The method for preparing polycrystalline carbonate cement according to claim 6, characterized in that: The conditions for natural curing are: ambient humidity of 50-60%, temperature of 20-25°C, and time of 24-48 hours.

Citation Information

Patent Citations

  • Low-calcium carbon-sequestration regenerated pervious concrete and production method thereof

    CN115557755A

  • Carbon sequestration type composite cementing material as well as preparation method and application thereof

    CN117069395A